Improving Speaking Skill Through Duet Version on Tiktok Application At The Eight Students Grade of Smp Negeri 4 Padangsimpuan - Nursaima Harahap; Rini Kesuma Siregar; Mei suhardo hutabarat (Rahis Cendekia Indonesia, 2025)
In collecting data, the writer gave a conversational text consisting of more than 20 vocabularies. After giving the text to the research sample, the writer documented the students' grades. Then the writer calculates it with a score. After getting the data, the next step that the writer takes is to analyze it using statistical analysis. From the average score obtained by students in the pre-test of 59.83. In posttest 1, the average score is 34.16. In addition, in posttest 2 the average value is 82.5. The percentage of decreased students' speaking ability between pretest and posttest 1 was -42.90. However, after carrying out the learning process followed by debriefing and training in speaking correctly, the percentage increase in implementation results between pre-test and post-test 2 was 37.89%